Multimodality OCT, IVUS and FFR evaluation of coronary intermediate grade lesions in women vs. men - Baruś, Piotr; Piasecki, Adam; Gumiężna, Karolina; Bednarek, Adrian; Dunaj, Piotr; Głód, Marcin; Sadowski, Karol; Ochijewicz, Dorota; Rdzanek, Adam; Pietrasik, Arkadiusz; Grabowski, Marcin; Kochman, Janusz; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background The pathophysiology of atherosclerotic plaque formation and its vulnerability seem to differ between genders due to contrasting risk profiles and sex hormones, however this process is still insufficiently understood. The aim of the study was to compare the differences between sexes regarding the optical coherence tomography (OCT), intravascular ultrasound (IVUS) and fractional flow reserve (FFR)-derived coronary plaque indices. Methods In this single-center multimodality imaging study patients with intermediate grade coronary stenoses identified in coronary angiogram (CAG) were evaluated using OCT, IVUS and FFR. Stenoses were considered significant when the FFR value was ≤0.8. Minimal lumen area (MLA), was analyzed by OCT in addition to plaque stratification into fibrotic, calcific, lipidic and thin-cap fibroatheroma (TCFA). IVUS was used for evaluation of lumen-, plaque- and vessel volume, as well as plaque burden. Results A total of 112 patients (88 men and 24 women) with chronic coronary syndromes (CCS), who underwent CAG were enrolled. No significant differences in baseline characteristics were present between the study groups. The mean FFR was 0.76 (0.73–0.86) in women and 0.78 ± 0.12 in men (p = 0.695). OCT evaluation showed a higher prevalence of calcific plaques among women than men p = 0.002 whereas lipid plaques were more frequent in men (p = 0.04). No significant differences regarding minimal lumen diameter and minimal lumen area were found between the sexes. In IVUS analysis women presented with significantly smaller vessel area, plaque area, plaque volume, vessel volume (11.1 ± 3.3 mm2 vs. 15.0 ± 4.6 mm2p = 0.001, 6.04 ± 1.7 mm2 vs. 9.24 ± 2.89 mm2p < 0.001, 59.8 ± 35.2 mm3 vs. 96.3 (52.5–159.1) mm3p = 0.005, 106.9 ± 59.8 mm3 vs. 153.3 (103–253.4) mm3p = 0.015 respectively). At MLA site plaque burden was significantly greater for men than women (61.50 ± 7.7% vs. 55.5 ± 8.0% p = 0.005). Survival did not differ significantly between women and men (94.6 ± 41.9 months and 103.51 ± 36.7 months respectively; p = 0.187). Conclusion The presented study did not demonstrate significant differences in FFR values between women and men, yet a higher prevalence of calcific plaques by OCT and lower plaque burden at the MLA site by IVUS was found in women vs. men.